2022
DOI: 10.3389/fpsyg.2022.957037
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing an art education program through immersive virtual reality or iPad: Examining the mediating effects of sense of presence and extraneous cognitive load on enjoyment, attention, and retention

Abstract: Sense of presence and extraneous cognitive load (ECL) are the two psychological effects widely employed to explain the cognitive outcomes caused by high-immersive media (e. g., virtual reality). This study identified the concepts of both technological affordance (i.e., immersion) and the psychological effects of VR learning. It investigated the mechanism by which immersion leads to better or worse communication in the context of art education. We operationalized the concept of immersion into two levels: a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Zhou et al (2020) found in their research that social presence in the live-streaming environment can make people feel accompanied by others and improve the subjective well-being of the audience [44]. Wang et al (2022) posited that the essence of live-streaming e-commerce is social commerce [45]. Consumers share product information and interact emotionally in the virtual space provided by live streaming to meet their purchase needs and emotional needs [46].…”
Section: Social Presence and Consumer Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (2020) found in their research that social presence in the live-streaming environment can make people feel accompanied by others and improve the subjective well-being of the audience [44]. Wang et al (2022) posited that the essence of live-streaming e-commerce is social commerce [45]. Consumers share product information and interact emotionally in the virtual space provided by live streaming to meet their purchase needs and emotional needs [46].…”
Section: Social Presence and Consumer Well-beingmentioning
confidence: 99%
“…Enjoyment refers to the degree of positive emotions that users feel when interacting with digital systems [51]. In the context of online live shopping, we regard enjoyment as shopping enjoyment, that is, the degree of positive emotion consumers feel when interacting with live-streaming media technology.…”
Section: The Mediating Role Of Shopping Enjoymentmentioning
confidence: 99%